PERANCANGAN INTERIOR RUANG MAKAN SANTRI PUTRI PONDOK PESANTREN AL MUJAHIDIN SAMARINDA - Sarah, Yuni; Nur Azizah, Sintya; Royanti, Royanti (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
Islamic boarding schools are Islamic institutions in Indonesia that are still trusted and in demand by the Indonesian people for elementary, middle, and high schools. Islamic boarding school facilities are also becoming more modern. Based on that, this research focuses on designing a dining room with an ergonomic and aesthetic concept to create an environment that supports the activities of the students. This research used qualitative research methodology, with the main data source being the Al-Mujahidin Samarinda Islamic Boarding School. The study was conducted for 3 months using data collection techniques through observation, interviews, and documentation. The results of this research were the design of the Al-Mujahidin Islamic Boarding School dining room design with a contemporary Islamic theme, with the use of Islamic motifs and patterns, as well as soft color palettes, the Islamic boarding school dining room becomes more than just a place to eat, the atmosphere of the room is rich in spiritual values, in line with Islamic boarding school values, it was successfully created through a combination of Islamic traditions and modern lifestyles. The circulation in this dining room also combines linear and radial by ensuring that efficient and flexible air circulation makes this room comfortable for students to carry out their activities. Stain-resistant wall materials such as paint and gypsum board for the ceiling created a clean, tidy, and comfortable room. Sufficient natural lighting and well-planned artificial lighting coupled with adequate ventilation and security facilities such as fire extinguishers, smoke detectors, sprinklers, and CCTV provide comfortable and safe protection in the Islamic boarding school environment. Apart from that, the research results also show the design of the dining room. to be more aesthetic and functional, by prioritizing accommodation for its residents’ spiritual, social, and practical needs.